Identification and prevalence of ectoparasites and endoparasites in kerandang fish Channa pleurophtalma and catfish Clarias batrachus captured from Sebangau River - Infa Minggawati; Frid Agustinus; Tania Serezova Augusta; Candra Putra Pahawang; Toto Francisco (Jurnal Akuakultur Indonesia, 2022)
ABSTRACT This study aimed to determine types, prevalence, and intensity of ectoparasites and endoparasites that infect kerandang fish Channa pleurophtalma and catfish Clarias batrachus. Sampling was carried out in Sebangau River, while identification was carried out at the Fish Quarantine, Quality Control, and Safety Station, Palangka Raya. Examination of ectoparasite infection included bilateral body mucus, caudal fin, and gills. Endoparasite examination was done by observing the fish organs, such as liver, blood, meat, intestines, and stomach. The parasite analysis was determined by calculating the prevalence and intensity. In kerandang fish, the ectoparasites were identified as Trichodina sp., Gyrodactylus sp., Epistylis sp., Dactylogyrus sp., while the endoparasites were Camallanus sp. and Neoechinorhyncus. In catfish, the ectoparasites were identified as Trichodina sp., Dactylogyrus sp., Myxobolus sp., and Costia sp., while the endoparasites were Camallanus sp. Dominant ectoparasite that infected fish was Dactylogyrus sp. on fish gills. For endoparasites, the dominant endoparasites were identified as Neoechinorhyncus in kerandang fish and Camallanus sp. in catfish. The highest prevalence was found in Dactylogyrus sp. at 27%. The prevalence was categorized as a frequent infection. The highest ectoparasite intensity level was obtained from Trichodina sp. at 20.3 ind/fish in kerandang fish and Dactylogyrus sp. at 12.2 ind/fish in catfish. This intensity level is categorized in a medium intensity. Keywords: Channa pleurophtalma, Clarias batrachus, ectoparasites, endoparasites ABSTRAK Penelitian ini bertujuan untuk mengetahui jenis ektoparasit dan endoparasit yang menginfeksi ikan kerandang Channa pleurophtalma dan ikan lele Clarias batrachus serta prevalensi dan intensitas parasitnya. Pengambilan sampel dilakukan di sungai Sebangau sedangkan identifikasi dilaksanakan di Stasiun Karantina Ikan, Pengendalian Mutu dan Keamanan Hasil Perikanan Palangka Raya. Pemeriksaaan infeksi ektoparasit meliputi; lendir tubuh bilateral, sirip ekor, dan insang. Pemeriksaan endoparasit dilakukan dengan cara mengamati bagian organ tubuh ikan seperti hati, darah, daging, usus, dan lambung. Untuk mengetahui tingkat serangan parasit pada ikan dianalisis dengan menghitung prevalensi dan intensitas. Pada ikan kerandang parasit yang teridentifikasi ektoparasit adalah Trichodina sp., Gyrodactylus sp., Epistylis sp., Dactylogyrus sp., dan endoparasit adalah Camallanus sp., dan Neoechinorhyncus. Pada ikan lele parasit ektoparasit yang teridentifikasi adalah Trichodina sp., Dactylogyrus sp., Myxobolus sp., dan Costia sp., sedangkan pada endoparasit adalah Camallanus sp. Ektoparasit yang dominan menginfeksi kedua ikan ini adalah Dactylogyrus yang terdapat pada insang. Sedangkan untuk endoparasit, pada ikan kerandang endoparasit yang dominan adalah Neoechinorhyncus dan endoparasit pada ikan lele adalah Camallanus sp. Prevalensi tertinggi pada ikan kerandang dan ikan lele adalah Dactylogyrus yaitu masing-masing 27%. Berdasarkan hasil prevalensi parasit pada ikan kerandang dan ikan lele termasuk kedalam kategori infeksi sering. Intensitas tertinggi pada ikan kerandang adalah Trichodina sp. dengan nilai 20.3 ind/ekor dan pada ikan lele adalah Dactylogyrus sp. dengan nilai intensitas 12.2 ind/ekor. Dari hasil intensitas parasit pada kedua ikan tersebut termasuk dalam kategori intensitas sedang. Kata kunci: Channa pleurophtalma, Clarias batrachus, ektoparasit, endoparasit